D'PAJ Sport Centre / Patrick Sullang Ambun … [et.al.]. - Ambun, Patrick Sullang; Jai, Azwan; Claisdell Lorren, Jeff Collven (2018)
D'PAJ Sport Centre is a company located in The Summer Mall in Kota Samarahan, Sarawak. D’PAJ Sport Centre expects to catch the interest of new customers with its world class sportwear distribution. The major of our business is providing high-technology of sportwear apparel gained from Adidas company and Nike company. The company plans to have strong market position in Kota Samarahan, due to great materials products and affordable price. D'PAJ Sport Centre aims to offer its products at a competitive price to meet customers' income. Especially, students from nearby universities and family who interest it wearing sportwear apparel. D’PAJ Sport Centre is equally owned and managed by its five (3) partners. The personals are Jeff Collven Anak Claisdell Lorren as General Manager and Financial Manager, Patrick Sullang Ambun as Marketing Manager, and Azwan bin Jai as Operational Manager and Administrative Manager. The products provided by the company are; Adidas Classic T-Shirt, Adidas Climalite and Adidas Climacool, Nike Training T-Shirt, and Nike Dri-Fit.